Calculation of the overturning wind speed of large road vehicles at exposed sites. Issue 6 (21st December 2020) - Baker, Chris J.; Soper, David
Abstract : High-sided vehicles are particularly vulnerable to high wind conditions and at sites that are regarded as vulnerable, a range of vehicle restrictions are imposed in high winds. These may include vehicle speed reductions or complete restrictions on the movement of different categories of vehicle at different wind gust speeds. This paper builds on earlier work that has been carried out and seeks to develop a simple but conservative method that can be used to specify vehicle restriction strategies. This is based on a collation of a wide range of data for aerodynamic rolling moment coefficients that allows a simple parameterisation to be developed. This is then used in an overturning model to develop a non-dimensional relationship between overturning gust speed and vehicle speed. The parameter used in the non-dimensionalisation is a characteristic wind speed that is a function of vehicle weight and geometry, and effectively specifies the vulnerability of the vehicle to overturning in high winds. Dimensional relationships between overturning gust velocities and vehicle velocities can thus be derived for different vehicle types and used to develop site-specific vehicle restriction methods.